TLR2 engagement on CD4(+)T cells enhances effector functions and protective responses to Mycobacterium tuberculosis - Reba, Scott M (2014)
We have previously demonstrated that mycobacterial lipoproteins engage TLR2 on human CD4(+) T cells and up-regulate TCR triggered- IFN-γ secretion and cell proliferation in vitro. Here we examined the role of CD4(+) T cell-expressed TLR2 in Mycobacterium tuberculosis (MTB) Ag-specific T cell priming and in protection against MTB infection in vivo. Like their human counterparts, mouse CD4(+) T cells express TLR2 and respond to TLR2 co-stimulation in vitro. This Th1-like response was observed in the context of both polyclonal and Ag-specific TCR stimulation. To evaluate the role of T cell TLR2 in priming of CD4(+) T cells in vivo, naïve MTB Ag85B specific TCR transgenic CD4(+) T cells (P25 TCR-Tg) were adoptively transferred into Tlr2(-/-) recipient mice that were then immunized with Ag85B and with or without TLR2 ligand Pam(3)Cys-SKKKK (P3CSK4). TLR2 engagement during priming resulted in increased numbers of IFN-γ secreting P25 TCR-Tg T cells one week after immunization. P25 TCR-Tg T cells stimulated in vitro via TCR and TLR2 conferred more protection than T cells stimulated via TCR alone when adoptively transferred before MTB infection. Our findings indicate that TLR2 engagement on CD4(+) T cells increases MTB-Ag specific responses and may contribute to protection against MTB infection.